FACING ISIS RETURNING FOREIGN TERRORIST FIGHTERS: INDONESIA PERSPECTIVE - Fauzia Gustarina Cempaka Timur; Yanyan M. Yani (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2019)
The presence of foreign terrorist fighters (FTF) in armed conflicts pose a series of problems for third countries, they become involved even though their country is not one of the warring parties. FTF cannot be ignored because of its association with the activities of international terrorist networks. The paper begins with a brief overview on how FTF is becoming a burning issue in Indonesia's national security. This paper argues that, globalization has played part in terms of making terrorism and radicalization spread easily throughout the world, including Indonesia. Hence, fighting terrorism in both the traditional or contemporary forms is not an easy task anymore. While tackling any practices of terrorism and radicalism is a main priority for many countries around the world, the growing number of FTF in recent years is a clear impact of unfinished government’s effort of fighting terrorism that already growing beyond borders. This paper use qualitative method and the data analysis was undertaken using phenomenology approach. This paper then reflects the complexity of how Indonesia facing its citizen who come back to the country as ISIS returning fighters. It concludes by analyzing the problem of fighting FTF returnees in Indonesia and suggesting how dealing with FTF returnees can be more effective by considering both domestic and regional factors.